What happened in the North? Servants and rural workers in Norway - Miscali, Monica (2017)
El objetivo del presente artículo consiste en estudiar las condiciones de los sirvientes rurales en Noruega desde el período preindustrial hasta la industrialización de mediados del siglo XIX. Se describe la evolución del papel y de las tareas de los sirvientes prestando atención a las transformaciones y el cambio que se produjo desde una sociedad rural a una sociedad industrial. Al mismo tiempo se atiende a la importancia respecto de las actividades de servicios desde una perspectiva demográfica. Además, se abordan los roles de género, las tasas de masculinidad, las diferencias entre sirvientes y sirvientas y las diferencias en el trato que éstos recibieron. Se contextualiza el caso noruego con otros ejemplos de Europa y se investiga si hubo similitudes o diferencias
The aim of this article is to investigate the situation of the rural servants in Norway from the preindustrial period, the rural Norway, to industrialisation in the middle of XIX century. I will summarise the research that has been carried out in Norway. In particular I will describe the evolution of the servant?s role and tasks, underlining the transformations and passages from an agrarian society to an industrial one and the importance of the service activities from a demographic prospective. Furthermore I will describe the gender roles, the sex-ratio, the differences between male and female servants and the differences in the treatment they received. I will contextualise the case of Norway and see if there were similitudes or differences in accordance with what happened in the rest of the Europe
Keywords: Noruega; Servicio domestico; Función de los criados; Tasas de masculinidad; Criados rurales; Norway; Domestic service; Servants role; Sex-ratio; Rural servants